2013
DOI: 10.1063/1.4820786
|View full text |Cite
|
Sign up to set email alerts
|

Blow-up phenomena for the weakly dissipative Dullin–Gottwald–Holm equation

Abstract: In this paper, we study the Cauchy problem for the weakly dissipative Dullin–Gottwald–Holm equation. We establish certain conditions on the initial datum to guarantee that the corresponding positive strong solutions blow up in finite time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
18
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 18 publications
2
18
0
Order By: Relevance
“…Later on, Zhang et al [1] obtained the precise blow-up scenario and established some blow-up results for strong solutions, as well as the blow-up rate of the wave-breaking solutions to (1.9). This result complements the early one in the literature, such as [35].…”
Section: Introductionsupporting
confidence: 88%
See 1 more Smart Citation
“…Later on, Zhang et al [1] obtained the precise blow-up scenario and established some blow-up results for strong solutions, as well as the blow-up rate of the wave-breaking solutions to (1.9). This result complements the early one in the literature, such as [35].…”
Section: Introductionsupporting
confidence: 88%
“…Wu and Yin [26] discussed the blow-up, blow-up rate and decay of solution to the weakly dissipative θ-type equation. Recently, Novruzov [35] considered blow-up phenomena the Cauchy problem for DGH Eq. (1.9) with weak dissipation and established certain conditions on the initial datum to guarantee that the corresponding positive strong solutions blow up in finite time.…”
Section: Introductionmentioning
confidence: 99%
“…Authors showed the simple conditions on the initial data that lead to the blow-up of the solutions in nite time or guarantee that the solutions exist globally. Later on, Zhang et al [2] improved the results of [1]. In [45], Novruzov extended the obtained "blow-up" result to the DGH equation under some conditions on the initial data.…”
Section: Introductionmentioning
confidence: 95%
“…Zhou, Mu and Wang [43] considered the weakly dissipative gCH equation (i.e (1.1) with c = , a = b + , k = ). Recently, Novruzov [1] studied the Cauchy problem for the weakly dissipative Dullin-Gottwald-Holm (DGH) equation (i.e (1.1) with N = , c = , b = , a = ) and establish certain conditions on the initial datum to guarantee that the corresponding positive strong solutions blow up in nite time. The same equation for arbitrary solution has been considered in [44].…”
Section: Introductionmentioning
confidence: 99%
“…The infinite propagation speed for the Camassa-Holm equation (and the two-component extensions of it) for k = 0 was investigated in [22,31,32,33,34] (see also [47] for k = 0). Also, the wide range of problems for CH equation with non-zero dispersion coefficient was considered in [40,54,47,46]. In particular, certain conditions on the initial datum to guarantee that the corresponding solution exists globally or blows up in finite time were established.…”
mentioning
confidence: 99%